Influence of acetylene on methane–air explosion characteristics in a confined chamber - Jinzhang Jia (Nature Portfolio, 2021)
Abstract To study the impact of acetylene on methane explosions, the safe operation of coal mines should be ensured. In this paper, a 20 L spherical tank was used to study the explosive characteristics of acetylene–methane–air mixture. In addition, the GRI-Mech3.0 mechanism was used to study the chemical kinetic mechanism for the mixed gas, and the effect of adding acetylene on the sensitivity of methane and the yield of free radicals was analysed. The results show that acetylene can expand the scope for methane explosion, lower the lower explosion limit, and increase the risk of explosion. Acetylene increases the maximum explosion pressure, laminar combustion rate and maximum pressure rise rate for the methane–air mixture while shortening the combustion time. Three combustion modes for the acetylene–methane–air mixture were determined: methane-dominated, transitional and acetylene-dominated combustion modes. Chemical kinetic analysis for the mixed gas shows that as the volume fraction of acetylene increases, the generation rate for key free radicals (H*, O* and OH*) gradually increases, thereby increasing the intensity of the explosive reaction. The results from this research will help formulate measures to prevent coal mine explosion accidents.